2007
DOI: 10.1074/jbc.m701314200
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis Cry1Ab Mutants Affecting Oligomer Formation Are Non-toxic to Manduca sexta Larvae

Abstract: Pore-forming toxins are biological weapons produced by a variety of living organisms, particularly bacteria but also by insects, reptiles, and invertebrates. These proteins affect the cell membrane of their target, disrupting permeability and leading eventually to cell death. The pore-forming toxins typically transform from soluble, monomeric proteins to oligomers that form transmembrane channels. The Cry toxins produced by Bacillus thuringiensis are widely used as insecticides. These proteins have been recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(120 citation statements)
references
References 57 publications
9
108
0
Order By: Relevance
“…Also, it was reported that Cry1Ab mutants in helix ␣-4 were affected in pore formation activity and were inactive. The mutants in helix ␣-4 are dominant-negative inhibitors of Cry1Ab toxin (5,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was reported that Cry1Ab mutants in helix ␣-4 were affected in pore formation activity and were inactive. The mutants in helix ␣-4 are dominant-negative inhibitors of Cry1Ab toxin (5,40).…”
Section: Discussionmentioning
confidence: 99%
“…The activated Cry toxins are globular molecules consisting of a bundle of seven ␣-helices (domain I), a three-␤-sheet prism (domain II), and a ␤-sandwich (domain III) (3,4). The N-terminal domain I is involved in oligomer formation, membrane insertion, and pore formation (5)(6)(7)(8). Domain II and III are involved in the recognition and binding interaction with receptors in midgut cells (9 -11).…”
mentioning
confidence: 99%
“…For monomer production, Cry1Ab crystals were solubilized in alkaline buffer and activated by trypsin as reported previously (24). In order to obtain oligomeric structure, the crystals were activated with 5% M. sexta midgut juice in the presence of scFv73 antibody as described (16 (7,25,26). These constructions were transformed into Escherichia coli ER2566 cells; protein expression was induced by the addition of 1 mM isopropyl-thio-␤-galactopyranoside.…”
Section: Methodsmentioning
confidence: 99%
“…Also, it was shown that binding with APN was in the range of 100 nM (20). We previously cloned and produced in E. coli two cadherin fragments corresponding to CR7-CR12 (residues Met 810 -Ala 1485 ) and to CR12 (residues Gly 1370 -Ala 1485 ) of M. sexta Bt-R1 (7,25,26). It was reported that Cry1Ab bound to a cadherin peptide (CR12-MPED) similar to CR12 with a binding affinity of 9.5 nM (34).…”
Section: Binding Assays Of Cry1ab Loop 3 Mutants With Bt-r 1 and Apn-mentioning
confidence: 99%
See 1 more Smart Citation